Functional disorders of the digestive tract in children: some aspects of correction - E.L. Krivusha; L.L. Petrenko (Zaslavsky O.Yu., 2018)
The article presents the main pathogenetic features of the development of functional disorders of the digestive tract in young children, as well as diagnostic criteria. A general description of Lactobacillus rhamnosus GG, the most studied probiotic strain in the world, is given, and the evidence of proven positive effects of bacteria on the macroorganism are presented. Pharmaceutical features of Active Flora baby, a new probiotic on the Ukrainian market, are described.